Th1/Th2 balance in the liver and hepatic lymph nodes of vaccinated and unvaccinated sheep during acute stages of infection with Fasciola hepatica - Pacheco Luque, Isabel; Abril, Nieves; Morales-Prieto, Noelia; Bautista, María José; Zafra, Rafael; Escamilla-Sánchez, Alejandro; Ruiz-Campillo, María Teresa; Martinez Moreno, Álvaro; Pérez, José (Elsevier B.V., 2017)
The expression of IFNγ and IL4 was quantified using q-PCR in the liver and hepatic lymph nodes (HLN) of sheep during early stages of infection with Fasciola hepatica (1, 3, 9 and 18days post-infection, dpi). A group of animals (Group 1) were vaccinated with Fasciola hepatica recombinant cathepsin L1 (FhCL1) in montanide 70 VG prior to infection, a second group (group 2) was used as infected control and a third (group 3) was used as uninfected control. To study vaccine efficacy three additional groups were sacrificed 19 weeks post-infection (group 4 immunized with CL1, group 5 with the adjuvant and group 6 was used as infected control). The vaccinated group did not show significant fluke reduction compared to the adjuvant group and infected control group. IL4 expression was observed to increase at 9 dpi and was further elevated at 18 dpi in the liver and HLN of vaccinated and infected control groups compared to the uninfected group. IFNγ expression exhibited different dynamics in the liver and HLN compared to IL4; thus, in the liver this cytokine increased at 9 dpi in the vaccinated and at 18 dpi in vaccinated and infected control groups, while in the HLN it decreased gradually and significantly from 1 dpi onwards. These results suggest that a marked Th2 polarization is present from 9 dpi in HLN and from 18 dpi in the liver. The increase of IFNγ in the liver may correspond with tissue damage response with granuloma formation. The FhCL1 vaccine did not alter the Th1/Th2 balance when compared to unvaccinated and infected sheep. The study of IFNγ and IL4 in the various tissue compartments in sheep could facilitate selection of new adjuvants inducing a strong Th1 response for a more rationale vaccine formulation.
Keywords: Fasciola hepática; Ovejas - Vacunación; Ovejas - Parásitos; Parasitología veterinaria - Aspectos inmunológicos; Parasitology; Immunopathology